Introduction to statistics for built environment. 1st ed. - Abu Hassan, Fatin Zahida; Mat Russ, Nazirah; Fauri @ Fauzi, Muhammad Zorif; Mohd. Basri, Mohd. Rafaei; Mohd. Jemoner, Samsul Rohaizad (Department of Architecture and Environmental Design, CFS, IIUM, 2023)
This book, Introduction of Statistics for Built Environment is specially prepared for students taking Foundation in Architecture and Environmental Design programme at Centre for Foundation Studies, IIUM Gambang Campus, Pahang. This book covers Basic Concept of Statistics, Variables and Measurement, Sampling Technique and Data Collection Method, Data Presentation, and commonly used Descriptive Analysis and Inferential Analysis. Each chapter begins with Learning Outcomes and an Introduction, while ends with Quick Exercise sections for students to check their understanding on each chapter and subchapters. The contents from this book have been explained in clear and detailed way, with various examples, table, graphic, and diagram. Examples and Model Examination Paper are also included that will enable students to practice the concept and formulae learnt. The answer for Quick Exercise and Model Examination Paper are also provided for students to self-check and revise, in preparation for the examination. We would highly thank everyone that has involved in the preparation and production of this book, and hope that this book would serve its purpose in aiding students to gain better understanding of the contents.